INVESTIGATION OF THE USE OF FACEBOOK IN SUPPORTING STUDENTS ENGLISH SELF-DIRECTED LEARNING - Mutiaraningrum, Ira; Salam, Urai; Novita, Dewi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstrak: Penelitian ini bertujuan untuk menginvestigasi penggunaan sebuah grup di Facebook yang bernama MAN XI IPA 1 English Club dan masalah yang dihadapi dalam penggunaannya sebagai media pendukung pembelajaran mandiri pada pelajaran Bahasa Inggris. Subjek dari penelitian ini adalah siswa kelas XI IPA 1 di MAN 1 Sintang. Dalam peneltian ini, penulis menggunakan metode studi kasus. Data dikumpulkan melalui angket dan wawancara. Data menunjukkan bahwa siswa melalui proses perencanaan (79,32%), penerapan (81,58%), dan evaluasi (78,41%) pembelajaran mandiri. Siswa mengadapi sedikit masalah pada penggunaan sumber belajar (38,26%), sedikit masalah pada perubahan strategi belajar (34,66%), alasan berpartisipasi dalam grup (42,05%) menjadi masalah utama yang mereka hadapi dimana mereka berpartisipasi sebatas yang diharuskan guru, dan sangat sedikit masalah pada konteks pembelajaran online (14,77%). Kata kunci: Pembelajaran mandiri, Pembelajaran Bahasa Inggris, pembelajaran online, Facebook Abstract: This research aims to investigate senior high school students use of facebook group named MAN XI IPA 1 English Club along with problems encountered while using the group as a media supporting English self-directed learning (SDL). The subject of this research were the students of XI IPA 1, MAN 1 Sintang. In this case study case study, the data were obtained from the questionnaire and interview. The data shows that the students went through the process of SDL including planning (79.32%) , implementation (81.58%), and evaluation (78.41%). This study reveals that the students experienced few problem in resource use (38.26%), problem in adjusting new teaching and learning strategies (34.66%), and problems in online contexts (14.77%). Meanwhile, the students problems in the motive of participating in the group (42.05%) was the major problem where the students only participate because of the course requirement. Key words: Self-directed learning, English language learning, Online learning, Facebook